EXPLORING DIFFERENTIATED LEARNING TO FOSTER CREATIVE THINKING: A STUDY ON STOICHIOMETRY IN SENIOR HIGH SCHOOL - Fahmi, Muhammad Rizal; Hakim, Fachri; Ningrum, Lis Setiyo (Jurnal Pendidikan Matematika dan IPA, 2026)
This research is based on the low ability of creative thinking in SMAN 1 Wedung. Learning can be optimal when students learn according to their learning styles. However, in reality, learning based on students' differing interests and learning styles is not well facilitated. This is due to several factors. The purpose of this study was to exploring differentiated learning to foster creative thinking on stoichiometry material in high school. This research is a quantitative research with a quasy experimental design of non-equivalent control group design. The sampling technique used cluster random sampling technique. The population of the research sample was all students in grade XI and the samples used in the study were class XI MIPA 1 and XI MIPA 2. Class XI MIPA 1 as the experimental class and class XI MIPA 2 as the control class. The research data were obtained through the pre-test and post-test results of the control and experimental classes which were then analyzed using the t- test test. Based on the final stage of data analysis, the results of hypothesis testing using the t-test on post-test data showed a significance value (2- tailed) of 0.000. Because the significance value (2- tailed) is smaller than 0.05, the alternative hypothesis (Ha) is accepted while the null hypothesis (Ho) is rejected. So it can be concluded that the differentiated learning model is effective for improving students' creative thinking skills in stoichiometry material.